1995
DOI: 10.1083/jcb.130.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a fibroblast marker: FSP1.

Abstract: Abstract. We performed subtractive and differential hybridization for transcript comparison between murine fibroblasts and isogenic epithelium, and observed only a few novel intracellular genes which were relatively specific for fibroblasts. One such gene encodes a filament-associated, calcium-binding protein, fibroblast-specific protein 1 (FSP1). The promoter/enhancer region driving this gene is active in fibroblasts but not in epithelium, mesangial cells or embryonic endoderm. During development, FSP1 is fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
801
1
15

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 972 publications
(839 citation statements)
references
References 60 publications
22
801
1
15
Order By: Relevance
“…To explore the role of S100A4 + cells in the development of CRC, S100A4-thymidine kinase (TK) transgenic mice were used, 22 , 39 and proliferating S100A4 + cells in these mice could be selectively depleted upon the treatment of ganciclovir (GCV) after the administration of AOM/DSS, as illustrated in Fig. 3A.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the role of S100A4 + cells in the development of CRC, S100A4-thymidine kinase (TK) transgenic mice were used, 22 , 39 and proliferating S100A4 + cells in these mice could be selectively depleted upon the treatment of ganciclovir (GCV) after the administration of AOM/DSS, as illustrated in Fig. 3A.…”
Section: Resultsmentioning
confidence: 99%
“…28 We double-stained the skin tissue with ␣-SMA and FSP1 and found that there were seldom ␣-SMA and FSP1 double positive cells in the TPA-treated skin ( Figure 1B), which is similar with the former discovery in the tumor, 29 indicating that TPA mainly simulated the proliferation of a unique population of FSP1 ϩ fibroblasts that are regarded as the most important class of fibroblasts present in many tissues. 20,30 FSP1 usually serves as a sensitive and specific marker for fibroblasts. 31 Recently, using FSP1 as the promoter in Cre-loxp system, Trimboli et al 32 described that Pten in stromal fibroblasts suppresses mammary epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, transitions do occur particularly during oncogenesis [31] and fibrogenesis [32,33]. This process has been particularly studied in renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%